Peculiar Features in Economical Efficiency Control of Main Equipment Operation of Automatic Control System for Technological Processes at Thermal Power Station - V. I. Nazarov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a target-oriented criterion that permits a power-unit operator remove fuel burn, that is originated in the process of equipment operation, with minimum losses.